IMPLICATIONS OF MOTIVATION FACTORS IN THE ACTIVITY OF ROMANIAN SPORTS TEACHERS - HULPUȘ IOANA; HULPUȘ ALEXANDRU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Work motivation is an important concept in human resources management that refers to the influence exerted by certain factors on employees, determining their positive or negative actions for the performance of work tasks. Starting from theoretical arguments based on the scientific literature, we proposed as the objective of the research the evaluation of the existing stimulation system in the pre-university education system, aimed at sports teachers. The research tried to determine to what extent the needs described by Maslow are motivating factors for sports teachers in the pre-university environment, but also to identify the main specific constraints that the staff face. At the same time, we aimed to investigate the implications of leadership and organizational culture on the level of motivation.